EFFECT OF PRE-OPERATIVE TRANEXAMIC ACID ADMINISTRATION ON POST-OPERATIVE HEMOGLOBIN LEVEL IN PERITROCHANTERIC FRACTURES - ABIDI, SAR; AHMED, I; RAZA, T; KHAN, AGS; ALSADOUN, L; ADEEL, M; GULZAR, W (Biological and Clinical Sciences Research Journal, 2024)
Peritrochanteric fractures, a common orthopaedic challenge, often necessitate surgical intervention to restore mobility and prevent complications in the elderly population. Despite advancements in surgical techniques, optimizing perioperative care remains critical to improving outcomes. Tranexamic acid (TXA), an antifibrinolytic agent, has effectively reduced blood loss and transfusion requirements in various surgical procedures. Objective: To assess the influence of pre-operative TXA administration on postoperative haemoglobin levels, intraoperative blood loss, transfusion rates, and adverse events in peri trochanteric fractures. Methodology: Employing a Prospective Double-Blind study design at Jinnah Medical College Hospital Karachi from January 2020 to January 2021. Ninety participants were enrolled: 45 in the experimental group and 45 in the control group. The AO/OTA Classification categorised fracture severity. The statistical analysis compared the baseline characteristics, postoperative outcomes, and adverse events across groups using t-tests for continuous variables and chi-square tests for categorical data. The main result, the haemoglobin levels after surgery, was examined using analysis of covariance (ANCOVA) to account for any factors that may affect the outcome. The study was performed using the statistical software SPSS (version 23.0). Results: Baseline characteristics, including age, gender distribution, BMI, and fracture severity, were comparable between groups. Post-operative haemoglobin levels were similar (Experimental: 11.5 ± 1.2 g/dL; Control: 11.9 ± 1.4 g/dL), but the experimental group exhibited significantly lower intraoperative blood loss (350 ± 50 mL vs 380 ± 60 mL, p=0.032). Transfusion rates were comparable (Experimental: 8.9%; Control: 11.1%), and adverse event incidences, including infections (Experimental: 6.7%, Control: 8.9%), thromboembolic events (Experimental: 2.2%, Control: 4.4%), and cardiovascular complications (Experimental: 4.4%, Control: 2.2%), were comparable, emphasising TXA’s safety profile. Conclusion: Pre-operative TXA administration in peritrochanteric fractures may effectively reduce intraoperative blood loss without adverse effects on post-operative haemoglobin levels or increased adverse event rates. These findings contribute valuable insights into the potential benefits of TXA in optimising surgical outcomes in this specific orthopaedic context.